2022
DOI: 10.3389/fmicb.2022.847653
|View full text |Cite
|
Sign up to set email alerts
|

Flammulinavelutipes Polysaccharides Modulate Gut Microbiota and Alleviate Carbon Tetrachloride-Induced Hepatic Oxidative Injury in Mice

Abstract: A carbon tetrachloride-induced acute liver injury mouse model is used to study the regulation of gut microbiota and hepatoprotective effect of polysaccharides from Flammulina velutipes (FVPs). The hepatoprotective effect of the FVPs leads to reduced levels of serum aspartate transaminase (AST), alanine aminotransferase (ALT), triglyceride (TG), total cholesterol (TC), total bile acid (TBA) content, and change in liver histopathology. Their anti-oxidant activity is exhibited by decreased levels of hepatic malon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The Fuzhuan brick tea polysaccharide contributed to the proliferation of beneficial microbiota, such as Lactobacillus and Akkermansia , and altered the Trp metabolism and elevated the fecal contents of IAld and IAA [ 48 ]. Flammulina velutipes polysaccharides (FVPs) also changed the composition of the gut microbiota, which affected the Trp metabolism [ 49 ]. The low abundance of Escherichia - Shigella , Dubosiella and Allobaculum , along with the enrichment of Muribaculaceae_unclassified , Ralstonia and Rikenellaceae_RC9_gut_group in the gut, which could result in higher Trp metabolite levels, could be detected in yellow wine polyphenolic compound-treated rats [ 50 ].…”
Section: Trp Metabolism In Gut Microbiotamentioning
confidence: 99%
“…The Fuzhuan brick tea polysaccharide contributed to the proliferation of beneficial microbiota, such as Lactobacillus and Akkermansia , and altered the Trp metabolism and elevated the fecal contents of IAld and IAA [ 48 ]. Flammulina velutipes polysaccharides (FVPs) also changed the composition of the gut microbiota, which affected the Trp metabolism [ 49 ]. The low abundance of Escherichia - Shigella , Dubosiella and Allobaculum , along with the enrichment of Muribaculaceae_unclassified , Ralstonia and Rikenellaceae_RC9_gut_group in the gut, which could result in higher Trp metabolite levels, could be detected in yellow wine polyphenolic compound-treated rats [ 50 ].…”
Section: Trp Metabolism In Gut Microbiotamentioning
confidence: 99%
“…Oxidative stress is considered the major cause of carbon tetrachloride–induced acute liver injuries (Xu et al, 2022). Glutamic acid, fumaric acid and malic acid are three important intermediates in the tricarboxylic acid (TCA) cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Jeotgalicoccus is positively correlated with insulin concentration in diabetic rats 52 . Atopostipes is enriched in carbon tetrachlorideinduced hepatic injury mice 53 . In summary, these data suggested that common dietary hydrophilic and hydrophilic emulsi ers demonstrated an adverse effect on gut microbiome homeostasis by elevating disease-associated bacterial genera and reducing the relative abundance of bene cial microbiomes.…”
Section: Discussionmentioning
confidence: 99%